Biochemical and biological characterization of wild-type and ATPase-deficient Cockayne syndrome B repair protein - Citterio, E; Rademakers, S; van der Horst, G T; van Gool, A J; Hoeijmakers, J H; Vermeulen, W (The Journal of biological chemistry, 1998)
Cockayne syndrome (CS) is a nucleotide excision repair disorder characterized by sun (UV) sensitivity and severe developmental problems. Two genes have been shown to be involved: CSA and CSB. Both proteins play an essential role in preferential repair of transcription-blocking lesions from active genes. In this study we report the purification and characterization of baculovirus-produced HA-His6-tagged CSB protein (dtCSB), using a highly efficient three-step purification protocol. Microinjection of dtCSB protein in CS-B fibroblasts shows that it is biologically functional in vivo. dtCSB exhibits DNA-dependent ATPase activity, stimulated by naked as well as nucleosomal DNA. Using structurally defined DNA oligonucleotides, we show that double-stranded DNA and double-stranded DNA with partial single-stranded character but not true single-stranded DNA act as efficient cofactors for CSB ATPase activity. Using a variety of substrates, no overt DNA unwinding by dtCSB could be detected, as found with other SNF2/SWI2 family proteins. By site-directed mutagenesis the invariant lysine residue in the NTP-binding motif of CSB was substituted with a physicochemically related arginine. As expected, this mutation abolished ATPase activity. Surprisingly, the mutant protein was nevertheless able to partially rescue the defect in recovery of RNA synthesis after UV upon microinjection in CS-B fibroblasts. These results indicate that integrity of the conserved nucleotide-binding domain is important for the in vivo function of CSB but that also other properties independent from ATP hydrolysis may contribute to CSB biological functions.